The Implementation of Undergraduate Students’ Critical Thinking on the Composition of Paper Essay in Paper Writing Class - Abror, Mochammad Abidin (RETAIN, 2021)
As one of the 21st-century skills, every student is required to acquire critical thinking skills. One way to investigate and encourage students' critical thinking is to assign them to write articles. Therefore, this study was conducted to determine how the students’ critical thinking is reflected in their paper writing and explore how they utilize their critical thinking to construct their paper writing. The objects of this study were six students’ paper writing results, and there were 15 students as the subjects in Paper Writing B Class in UNESA. This study used two main instruments to discuss two research objectives: the students’ paper writing results and the critical thinking rubric proposed by Ball State University and the questionnaire. In addition, the researcher also used unstructured format interviews as a complementary instrument to support the data obtained from the questionnaire. This study used descriptive qualitative as the research design. The results of this study showed that critical thinking had been reflected in the students' paper writing, specifically in synthesizing and paraphrasing. Furthermore, it was discovered that the students used critical thinking to develop their paper writing and determine appropriate solutions to tackle the problems they encountered while developing their writing.